2020
DOI: 10.1039/d0cy00154f
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-resolved investigation of the water inhibition of methane oxidation over palladium

Abstract: Pd/Al2O3 catalysts are known to be active for low temperature methane oxidation reactions, however it has been shown that gases normally associated with methane gas streams (H2O, CO2, H2S) can have an inhibitory effect on the total oxidation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 106 publications
1
12
0
Order By: Relevance
“…The attempts carried out on the Cu catalyst showed that the deactivation of the catalyst under the influence of water appears to be reversible. A similar effect was noticed in [103] for Pd/Al 2 O 3 where the inhibition process was partially reversible above 400 • C. In [104], it was shown that dispersion of the Pd phase also influences the deactivation of the catalyst, which stays in contact with water. The lower dispersion of Pd and the higher the water concentration in the feed stream, the stronger the inhibiting effect observed.…”
Section: Poison Resistance and Stability Testssupporting
confidence: 67%
“…The attempts carried out on the Cu catalyst showed that the deactivation of the catalyst under the influence of water appears to be reversible. A similar effect was noticed in [103] for Pd/Al 2 O 3 where the inhibition process was partially reversible above 400 • C. In [104], it was shown that dispersion of the Pd phase also influences the deactivation of the catalyst, which stays in contact with water. The lower dispersion of Pd and the higher the water concentration in the feed stream, the stronger the inhibiting effect observed.…”
Section: Poison Resistance and Stability Testssupporting
confidence: 67%
“…So far, several mechanisms have been reported for the deactivation mechanism of CH 4 combustion by H 2 O. In particular, it has been suggested that the adsorption of OH/H 2 O species on active PdO reduces the number of active sites that could participate in the CH 4 activation, ,− while the accumulation of OH/H 2 O species on the catalyst supports may impair the oxygen supply between Pd and the support. In addition, at high temperatures (>500 °C), sintering of PdO particles was induced in the presence of H 2 O vapors. ,, Therefore, the selection of the appropriate catalyst support is important for the development of highly active Pd catalysts for CH 4 combustion under wet conditions. So far, Pd catalysts with good hydrothermal durability have been developed using ZrO 2 . , The addition of CeO 2 , which has high oxygen mobility, suppressed the negative effect of H 2 O on the activity, while the SnO 2 support promoted the release of OH species from the active PdO surface and exhibited high activity even in the presence of H 2 O .…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed description is available in literature. 25 Fig. 1 Idealised conversion versus temperature for various aging phenomena; reprinted with permission from ref.…”
Section: Methodsmentioning
confidence: 99%